2007
DOI: 10.1212/01.wnl.0000267842.85646.f2
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of face expertise in the social developmental disorders

Abstract: Background:Patients with social developmental disorders (SDD), also known as autism spectrum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 82 publications
1
14
0
1
Order By: Relevance
“…When tested, patients with DP may have normal structural magnetic resonance imaging scans and may respond to faces with functional magnetic resonance activation in the fusiform face area (Avidan et al, 2005); however, there is much evidence that DP is associated with impaired configural processing of faces very similar to fusiform face area dysfunction (Barton et al, 2003, 2007a, 2007b; Huis in ‘t Veld et al, 2012). Because of this configural impairment, people with DP may revert, as did our participants, to sequential feature-by-feature inspection, particularly of salient features such as clothing, hairstyle, and eyebrows (Duchaine, 2000; Duchaine and Nakayama, 2004; Michelon and Biederman, 2003; Stollhoff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When tested, patients with DP may have normal structural magnetic resonance imaging scans and may respond to faces with functional magnetic resonance activation in the fusiform face area (Avidan et al, 2005); however, there is much evidence that DP is associated with impaired configural processing of faces very similar to fusiform face area dysfunction (Barton et al, 2003, 2007a, 2007b; Huis in ‘t Veld et al, 2012). Because of this configural impairment, people with DP may revert, as did our participants, to sequential feature-by-feature inspection, particularly of salient features such as clothing, hairstyle, and eyebrows (Duchaine, 2000; Duchaine and Nakayama, 2004; Michelon and Biederman, 2003; Stollhoff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a modification of the method reported by Barton et al (2007a), we showed participants front-view photographs of 20 anonymous (non-famous) individuals taken from public sources. We presented the photographs one at a time.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, analysis of visual social stimuli and/or their evaluation as social signals may be impaired (Williams et al 2008 ). Autism spectrum disorder: Facial confi guration and eye gaze processing (Barton et al 2007 ;Hoehl et al 2009 ), facial identity recognition, and general visual recognition (Wilson et al , 2012, biological motion perception (Nackaerts et al 2012 ), visual exploration (Ozonoff et al 2008 ) have all been described as being defi cient. Features of 'dorsal stream dysfunction' have also been described (MacIntyre-Béon et al 2010 ).…”
Section: Disorders Of Brain Developmentmentioning
confidence: 99%
“…In this perspective, tasks asking neurotypical individuals to assess the sameness of two faces usually report poorer performance when the standard spatial relation between the parts is distorted, as for upside-down faces (Valentine, 1988), composites made of two aligned half-faces from different people (Young et al, 1987), or faces with scrambled parts (Tanaka and Farah, 1993). However, studies implementing the same tasks in individuals with ASD have reported mixed findings with some describing them as not influenced (Van Der Geest et al, 2002; Joseph and Tanaka, 2003; Teunisse and de Gelder, 2003; Rondan and Deruelle, 2004; Riby et al, 2009) or less influenced than Controls (Hobson et al, 1988; López et al, 2004; Barton et al, 2007; Pellicano et al, 2007, see also Weigelt et al, 2012), but others describing equal effects as in neurotypical individuals (Teunisse and de Gelder, 2003; Rouse et al, 2004; Lahaie et al, 2006; Gross, 2008). Such variability could reflect the important heterogeneity of the ASD population, in which diagnostic symptoms are expressed differently across individuals, maybe confounded by age or attentional factors (Rondan and Deruelle, 2007), and/or possibly stem from the development of compensatory neuronal mechanisms (Gaigg, 2012; Dickstein et al, 2013).…”
Section: Introductionmentioning
confidence: 99%